LUMPUR AKTIF MENGUNGGULI EFFECTIVE MICROORGANISM-4 SEBAGAI STARTER PENGOMPOSAN SAMPAH DEDAUNAN DI RSUP DR. SARDJITO YOGYAKARTA - Rezania Asyfiradayati; Dwi Linna Suswardany; Dwi Astuti (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2012)
ABSTRACT Waste of activated sludge resulted by Dr. Sardjito Hospital needs to be used as a stimulator in order to get a lot of compost. Therefore, it needs other materials as a basic material for composting namely leaf litters taken from the hospital’s park. The objective of this research was to know the differences of time, pH, temperature and Nitrogen, Phosphat and Kalium content of compost with addition of EM-4 and activated sludge waste. Method of this research was experiment with posttest only control group design. Population of this research was all leaf litters taken from park of RSUP Dr. Sardjito weighting of 40 kg. Samples were 27 kg litters; EM-4 and active sludge waste treatment. Every experiment was repeated 3 times. Statistical test used in this research was One-way ANOVA. Result of the research indicated that there were differences of time and temperature but there was no difference pH between compost added with EM-4 and activated sludge waste, whereas there was a significant difference of NPK content between compost added with EM-4 and activated sludge waste. Results of laboratory test on EM-4-added compost indicated average content of N=1,17%, P=0,127%, and K=0,79%. Whereas on activated sludge waste-added compost contained average content of NPK as much as 2,28%; 0,217% and 1,993%. As a suggestion, Dr. Sardjito Hospital needs to use leaf litters as compost and waste of activated sludge as a stimulator. In addition, the resulted compost could be sold. Key words: activated sludge waste, Composting, EM-4, Leaf Litters, Dr. Sardjito Hospital Kesmasindo Volume 5, Nomor 2, Juli 2012, hlm. 136- 153